Evaluation of Po River water quality in Torino (Italy): Effects of diffuse and local point loads. Issue 6 (17th August 2016) - Panepinto, Deborah; Marchese, Franco; Genon, Giuseppe
Abstract : The aim of this paper is to examine the Po River water quality in a small stretch in Piedmont (northern Italy). In this stretch a large pollution load, derived from the wastewater treatment plant of Torino area (more than 2 million inhabitants), is discharged and diluted in the water. In this study this load has been quantified and modeled in order to understand the sources, destinations and effects of the emitted pollutants. The objective was to determine the impact produced by the Torino Wastewater Treatment Plant on the quality of the water, based on various hydrological conditions and the possible intervention on the point and diffuse loads.